Brief remission of cardiac conduction defect under anaesthesia during trans-sphenoidal pituitary surgery - Kaur, Kirandeep; Kaur, Manpreet; Mahajan, Shalvi (International Journal of Basic & Clinical Pharmacology, 2023)
Acromegaly can cause paroxysmal arrhythmia and bundle branch blocks, which may or may not be symptomatic. Physiological stress induced by anaesthesia can exacerbate cardiac problems; nevertheless, reversal of such problems can also occur despite being uncommonly reported. We describe temporary remission of left bundle branch block (LBBB) to normal sinus rhythm under general anaesthesia.